Currículo e infância: a construção de identidades de gênero na educação infantil - EVANGELISTA, Elicléia Silva (2019)
This paper titled "Curriculum and childhood: the construction of gender identities in early childhood education", is the result of a survey carried out at the Municipal School of Elementary Education and education Pedro Ferreira Costa, located in the urban area of Municipality of Abaetetuba - Pará, in which the relationship between the curricular practices of the period II of early childhood education was problematized in the construction of gender identities. The objective of this research was to highlight gender approaches in legislations and public policies of early childhood education and discuss the relationship between curricular practices in the construction of gender identities in the period II of childhood education. The research is of qualitative character based on Chizzotti (2001), and developed through an ethnographic case study based on André (2010), with techniques of data collection as participant observation according to Chizzotti (2001), interview Semistructured according to André (2010) and analysis of documents such as laws, resolutions, opinions, curriculum, school texts and others according to Mazzotti and Gewandsznajder (2002). The theoretical framework was inspired by the post-structuralist strand of cultural studies based on studies on the identity and curriculum of Tomaz Tadeu da Silva (1996, 2010, 2000a), of the gender theories of Joan Scott (1995, 2005), Guacira Louro (1994, 1997, 2000, 2001, 2004), Jimena Furlani (2011), Ana Camargo and Cláudia Ribeiro (1999) and others and the idea of power theorized by Michel Foucault (1979, 1987) through which data analyses were carried out. The results indicated that of the legal documents related to Early Childhood Education analyzed, only the National Curriculum Guidelines for Early Childhood Education and the National Curricular Common Base for the Early Childhood stage cite the word gender, and the second document states that they should still be formulated norms about gender identity, highlighting how the subject is not considered important and that the lack or lack of space given to gender issues in the main education legislations reflects directly in the curriculum development and consequently in the teaching offered by the school institutions that will continue to construct and reproduce the historical hierarchies and inequalities between boys and girls. This fact can be confirmed by following the curricular practices of period II researched that make use of several artifacts such as books of children's literature, toys, games among others that with their own cultural pedagogies also teach and through the reproduction of social discourses and norms of the behaviors present in the teachers' speeches, both showed that the construction of gender identities happens in a stereotyped, dichotomous, sexist, hierarchical way and in relations of inequalities that can cause limitations of opportunities, prejudices, discrimination and other types of violence that hurt the rights and impede the exercise of citizenship. It is therefore notable that there is a need to include gender issues in educational legislation so that it is present in teacher training and to be part of the curriculum of each year of teaching and effectively enable differentiated pedagogical proposals that promote gender equity and combat unequal relationships.